Deconstruction of Mandala’s Puri Agung Karangasem - Agus Kurniawan; P Rumawan Salain; N K Acwin Dwijendra; I G N Anom Rajendra (International Journal of Engineering and Emerging Technology, 2019)
Abstract-Deconstruction is a method, a thought as well as a theory created by Jacques Derrida, a philosopher and critic of French literature. Derrida himself was reluctant to determine exactly what deconstruction is. Derrida only mentions what is not, not what is yes. However, the thought that is currently on the decline is actually attracting the attention of architects so that his fame is revived. If you follow Derrida's way of thinking surely no one will be able to explain what deconstruction is, because once he explains that the deconstruction revealed is not deconstruction. To better recognize and understand the strategy of deconstruction in architecture, the way Bennedikt should be imitated, as a method of analyzing architectural works using the perspective of deconstruction. In this paper we will try to read an architectural work, using Bennedikt's method. The work that will be the object of reading is Puri Agung Karangasem. The main objective to be obtained through this paper is to find out whether the work can be classified into deconstruction architecture, to deepen the understanding of deconstruction itself and at the same time train sensitivity in thoroughly reviewing an architectural work through an observation angle.